Capacity Development of Minimum Service Standards Costing and Implementation - World Bank (2013)
Minimum Service Standards (MSS) in Indonesia is a measurement for evaluation of the local government performance in the implementation of obligatory functions related to basic services. The combination of obligatory functions, accompanied by MSS, aim to provide access for citizens at the minimum level of quality at a given time. The frameworks of MSS were developed started in early 2000 in respond then Law 32/2004 been intensively developed in Indonesia following the issuance of Law 32/2004 which stated in Articles 11 and 12 that while measuring the performance of obligatory functions government will refer to a MSS. These provisions are elaborated, which is defines MSS as a measurement of a type and quality of basic public service that all citizens have the right to receive. The program is a Government of Indonesia (Directorate General Bangda, MoHA) initiative, supported in its implementation by Decentralization Support Facility (DSF)/World Bank. With a view to improving the accessibility and quality of basic public services, the program supports the implementation of the minimum service standards by building government capacity to cost and implement MSS in the regions. The objectives of the program are to: strengthen MoHA capacity to work with other ministries, to cost MSS for selected sectors; improve central and provincial government support to district/city for MSS implementation; develop local government capacity for implementing MSS for selected sectors; and analyze factors underlying the successful implementation of MSS and possible relationships with the achievement of the Millennium Development Goals (MDGs).